An evaluation of the potential for drug–drug interactions between bendamustine and rituximab in indolent non-Hodgkin lymphoma and mantle cell lymphoma - Darwish, Mona (Springer Berlin Heidelberg, 2014)
PURPOSE: Bendamustine plus rituximab has been reported to be effective in treating lymphoid malignancies. This analysis investigated the potential for drug–drug interactions between the drugs in patients with indolent non-Hodgkin lymphoma or mantle cell lymphoma. METHODS: Data were derived from a bendamustine–rituximab combination therapy study, a bendamustine monotherapy study, and published literature on rituximab monotherapy and combination therapy. Analysis of the potential for rituximab to affect bendamustine systemic exposure included comparing bendamustine concentration–time profile following monotherapy to that following combination therapy and comparing model-predicted Bayesian bendamustine clearance in the presence and absence of rituximab. Analysis of the potential for bendamustine to affect rituximab systemic exposure included plotting observed minimum, median, and maximum serum rituximab concentrations at the end of rituximab infusion (EOI) and 24 h and 7 days post-infusion in patients receiving combination therapy versus concentrations reported in literature following rituximab monotherapy. RESULTS: The established population pharmacokinetic model following bendamustine monotherapy was evaluated to determine its applicability to combination therapy for the purpose of confirming lack of pharmacokinetic interaction. The model adequately described the bendamustine concentration–time profile following monotherapy and combination therapy in adults. There was no statistically significant difference in estimated bendamustine clearance either alone or in combination. Also, rituximab concentrations from EOI to 24 h and 7 days demonstrated a pattern of decline similar to that seen in rituximab studies without bendamustine, suggesting that bendamustine does not affect the rituximab clearance rate. CONCLUSIONS: Neither bendamustine nor rituximab appears to affect systemic exposure of the other drug when coadministered.